Bosnia and Herzegovina : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses key findings of the Financial System Stability Assessment on Bosnia and Herzegovina (BiH). Economic and financial activity in BiH remains stuck in a low gear since the global financial crisis, reflecting weak external demand, tighter funding conditions, and deep-seated structural issues. Aggregate solvency and liquidity indicators appear broadly sound, but significant pockets of vulnerability exist. The banking system is more than 80 percent foreign-owned banks. The average regulatory capital adequacy ratio exceeded 16 percent as of end 2014. Decisive and timely actions to deal with weak banks are critical for preserving financial stability.